Information technology in bio- and medical informatics : 7th International Conference, ITBAM 2016, Porto, Portugal, September 5-8, 2016, Proceedings /: 7th International Conference, ITBAM 2016, Porto, Portugal, September 5-8, 2016, Proceedings. (2016) - Unknown
No abstract available